Pelaksanaan Sistem Pembiasaan Untuk Menguatkan Hafalan Doa Terhadap Anak Umur 5-6 Tahun: Pelaksanaan Sistem Pembiasaan Untuk Menguatkan Hafalan Doa - Jimi Harianto; Sugiyati Sugiyati; Lilis Siti Aisah; Umil Luthfina (Apik Cahaya Ilmu, 2025)
This community engagement project addresses the critical need to foster spiritual values during early childhood, identifying proficiency in daily prayers as a foundational element of character development in young learners. The study evaluates the effectiveness of a structured habituation framework in supporting the memorization of daily supplications among children aged 5–6 at the Nusa Indah Sukamulya Playgroup (Kober) during the 2025–2026 academic year. The research utilizes a qualitative phenomenological approach, incorporating participant observation and semi-structured interviews for data collection, followed by thematic analysis using data reduction techniques. The findings highlight the creation of a systematic instructional design for prayer habituation, its staged integration into daily teaching routines (including introduction, core activity, and reflection), and the implementation of an assessment strategy that uses positive reinforcement through customized star stickers tailored to individual developmental milestones and cognitive abilities. The results indicate that a carefully structured, consistently implemented, and adaptively evaluated habituation system substantially improves prayer retention and fosters intrinsic motivation in children. This framework thus provides a promising model for innovative pedagogical practices to enhance spiritual literacy in early childhood education. Keywords: Implementation, Habituation System, Memorization of Prayer